The Palgrave Handbook of Musical Theatre Producers
XVIII, 559 p.
Keywords: This handbook is the first to provide a systematic investigation of the various roles of producers in commercial and not-for-profit musical theatre. Featuring fifty-one essays written by international specialists in the field, it offers new insights into the world of musical theatre, its creation and its promotion. Key areas of investigation include the lives and works of producers whose work is part of a US and worldwide musical theatre legacy, as well as the largely critically-neglected role of the musical theatre producer in the making, marketing, and performance of musicals. Also explored are the shifting roles of producers in musical theatre and their popular portrayals, offering a reader-friendly collection for fans, scholars, students, and practitioners of musical theatre alike.